The Pragmatics of Perception and Cognition in MT Jeremiah 1:1-6:30 A Cognitive Linguistics Approach - Hayes, Elizabeth R. 1952- (Berlin, New York Walter De Gruyter, 2008)
Biographical note: Elizabeth R. Hayes, University of Oxford, Bothell, USA.
Main description: Perception and cognition – seeing, hearing and understanding – are main themes in the Biblical Hebrew text of Jeremiah 1:1-6:30. This volume examines the text using a cognitive linguistics approach. This recently developed approach allows the modern reader to more fully understand the ancient text by observing aspects of embodied experience that are shared across time, space and culture, such as image schemas, conceptual metaphor and more elaborate conceptual blends. In addition to offering insights into some key textual disjunctions, these findings contribute towards reading and understanding the final form of the text.
Includes bibliographical references (p. [239]-252) and indexes
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Textual; Bible -- Language, style; Bible -- Grammar; Cognitive grammar; Hebrew language -- Grammar; Old Testament -- Biblical Interpretation -- Cognitive Linguistics -- Prophets, Jeremiah; RELIGION / Biblical Criticism & Interpretation / Old Testament; Altes Testament; Jeremia; Interpretation; Kognitive Linguistik; Propheten; FOREIGN LANGUAGE STUDY / General; Prophets; Jeremiah; HISTORY / Middle East / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Old Testament; RELIGION / Biblical Reference / Language Study; Biblical Interpretation; Cognitive Linguistics; Prophets, Jeremiah; Hochschulschrift